Women in Engineering: The Role of Role Models - M. Agurto; M. Bazan; S. Hari; S. Sarangi (Global Labor Organization (GLO), 2021)
Gender disparities in STEM fields participation are a major cause of concern for policymakers around the world. In addition to talent misallocation, low female enrollment rates in STEM careers contribute to gender-based inequalities in earnings and wealth, given the higher average level of earnings in these fields. This paper studies the effects of exposure to role models on female preferences for STEM majors. We conduct a randomized control trial where female senior students currently enrolled in engineering programs at an elite private university in Peru give talks about their experiences at randomly selected high schools. We find that exposure to this treatment increases high ability female students' preferences for engineering programs by 14 percentage points. The effect is only statistically significant for the subgroup of female students with baseline math scores in the top 25 percentile, and who reside close to the city where the role models' university is located. We also find positive but smaller effects on "low ability" male students. In a context where females are discouraged from enrolling in STEM fields, our results have important policy implications.
Keywords: C93; I23; I24; J16; 330; Enrollment gender gap; field experiment; role models; Higher Education; career choices; stereotypes